Evolution of Ukrainian Annual National Program since 2015 as response to changing information environment and hybrid threats - Izhutova , Iryna (Social Development and Security, 2020)
This article aims at researching the evolution and change of structure and content of the Ukrainian Annual National Program (ANP) since 2015 as response to ongoing hybrid warfare and addressing new hybrid threats. Strategic Communications are in focus of the research. It is underscored the flexibility of the program in line with ongoing reforms in Ukraine which cover all the spheres.